Llama Llama loose tooth drama - Dewdney, Anna (Viking, 2020)
"Llama Llama's tooth is wiggling! Is it time for his first tooth to come out? He's excited, but anxious. Who is this tooth fairy everyone talks about? Mama Llama reassures him; the tooth will come out when it's good and ready. But no one is ready for what happens next ... Suddenly, the tooth is GONE! Where did it go? And will the tooth fairy come at all, now?"--